Immersive performance and somatic practices: Joan Davis and the Maya Lila project. Issue 2 (1st December 2017) - Meehan, Emma
In this article, I focus on the work of Irish choreographer Joan Davis in order to draw out a debate on the value offered by somatic movement approaches to the field of immersive performance. Such works immerse audiences and performers in sensory, site-based and participatory performance. There has been a recent surge in the popularity of immersive theatre experiences and scholarship on this topic, with the writings for example of Alston, Harvie, Machon and White examining issues such as the agency of audience members and the relationship between individual freedom and group responsibility. What do somatic performances, which often physically immerse participants in outdoor environments, found spaces or designed installations, have to offer this field of theory and practice? Drawing on ideas in environmental theatre and performance ecology, including the work of Reeve, Kershaw and Schechner, I explore the relationship between people, sites, objects and wildlife in somatic performances as part of a whole ecology in shifting negotiation. I propose that although active, individual, experiential participation is part of these performances, body– mind reflective engagement in relationship to context is a vital contribution that somatics can offer to immersive practice more generally. This will be discussed in relation to Joan Davis' Maya Lila project (2002–15), as she invites participants to become aware of their behaviours within installation environments, as a means to explore being within and separate from a community, and challenging expectations, perceptions and actions.